First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations THE PEOPLE'S LEAGUE OF HEALTH. BALANCE SHEET, from 1st July to 31st December, 1920 LIABILITIES £ s. d. £ s. d. CREDITORS— Rent 3 0 0 Low Costs 22 9 0 25 9 0 GUARANTEE FUND SUBSCRIPTIONS 118 18 0 INCOME AND EXPENDITURE ACCOUNT — Balance 1st July, 1920, brought forward 363 8 10 Less Expenditure in excess of Income for half-year to date per Income and Expenditure Account 204 17 0 158 11 10 £302 18 10 ASSETS. £ s. d. £ s. d. CASH AT BANKERS London County Westminster and Parr's Bank, Ltd., Hanover Square — No. 1 Account 114 3 7 No. 2 Account 35 0 0 Deposit Account 120 0 0 269 3 7 CASH IN HAND 3 15 3 TYPEWRITERS, at Cost 36 8 6 Less Depreciation written off 6 8 6 30 0 0 £302 18 10 (Signed) F.N. CURZON, Hon. Treasurer „ OLGA NETHERSOLE, Hon. Organiser. „ G.M. HOLMES, Secretary. REPORT OF THE AUDITORS.— We have examined the foregoing Account of Income and Expenditure and the above Balance Sheet with the books and vouchers, and have obtained ah the information and explanations we have required. In our opinion the Balance Sheet is properly drawn up so as to exhibit a true and correct view of the state of the League's affairs, according to the best of our information and the explanations given to us as shown by the Books. 3, CROSBY SQUARE, E.C.3. EDWARD MOORE & SONS, Chartered Accountants. March 22nd, 1921 Honorary Auditors. 200/B/3/2/C693/1/71